2004
DOI: 10.1248/bpb.27.723
|View full text |Cite
|
Sign up to set email alerts
|

Danthron Inhibits the Neurotoxicity Induced by Various Compounds Causing Oxidative Damages Including .BETA.-Amyloid (25-35) in Primary Cortical Cultures

Abstract: Alzheimer's disease (AD) is known to induce deficits in learning and memory in older patients. The neuropathological hallmarks of AD are senile plaques and neurofibrillary tangles containing b-amyloid protein.Although the neurodegenerative mechanism of AD remains unclear, oxidative insults are important factors in the acceleration of neuronal death. 1) Some investigators have reported that b-amyloid itself does not directly contribute to the pathway of oxidative stress. 2,3) However, other investigators have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Amyloid-β and MPP+ are of particular importance in that amyloid-β toxicity is considered to be a model of Alzheimer's disease (Gotx et al, 2004) and MPP+ of Parkinson's disease (Gerlach and Riederer, 1996). The common point for BMAA potentiation of these injuries may be that amyloid-β (Kwon et al, 2004) and MPP+ (Johannessen et al, 1986) are known to induce oxidative stress, as do exposure to NMDA, Fe, and BSO (Dugan et al, 1995;Lobner et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid-β and MPP+ are of particular importance in that amyloid-β toxicity is considered to be a model of Alzheimer's disease (Gotx et al, 2004) and MPP+ of Parkinson's disease (Gerlach and Riederer, 1996). The common point for BMAA potentiation of these injuries may be that amyloid-β (Kwon et al, 2004) and MPP+ (Johannessen et al, 1986) are known to induce oxidative stress, as do exposure to NMDA, Fe, and BSO (Dugan et al, 1995;Lobner et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that human melanosis coli was induced in the large intestine of guinea pig followed by daily oral administration of the anthraquinone danthron then led to cause a transient, dose-related wave of apoptosis of the colonic surface epithelial cells [7]. Treatment with danthron may, in part, reduce neurotoxicity related to betaamyloid protein by both dominant inhibitory effects on membrane lipid peroxidation and glutathione deprivation in primary cortical cultures [8]. There are no report to address danthron-induced apoptosis in human cancer cells and also no available information regarding the possible pathway for danthron-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, danthron was ineffective against zinc toxicity, O 2 − radicals, N -methyl-𝒟-aspartic acid, kainate, staurosporine (STS), or dextromethorphan. 14 …”
mentioning
confidence: 99%